Principal Leadership and Teacher Discipline with Teacher Professionalism at Public Middle Schools in Parlilitan District, Humbang Hasundutan Regency - Saragih, Meysi Grace; Gea, Ibelala; Marbun, Rencan; Aritonang, Oktober Tua; Sitorus, Hisardo (Journal of Educational Analytics, 2024)
This study aims to determine the relationship between Principal Leadership and Teacher Discipline with Teacher Professionalism at Public Junior High Schools in Parlilitan District, Humbang Hasundutan Regency, both simultaneously and partially, with the hypothesis that there is a positive and significant relationship between Principal Leadership and Teacher Discipline with Teacher Professionalism at Public Junior High Schools in Parlilitan District, Humbang Hasundutan Regency. This study uses a quantitative method approach. The population in the study were all teachers of Public Junior High Schools in Parlilitan District, totaling 104 people with a sample of 76 people. The research instrument was a closed questionnaire, which was compiled by the researcher based on the research variable indicators. The questionnaire trial was conducted on 30 people who were not research samples, and has been tested with validity and reliability tests. This shows that there is a positive and significant relationship between Principal Leadership and Teacher Professionalism at Public Junior High Schools in Parlilitan District, Humbang Hasundutan Regency. Based on the research results, it can be concluded that there is a positive and significant relationship between Principal Leadership and Teacher Discipline with Teacher Professionalism at Public Middle Schools in Parlilitan District, Humbang Hasundutan Regency, both simultaneously and partially.